How do Covid-19 stay-at-home restrictions affect crime? Evidence from Rio de Janeiro, Brazil - Jessie Bullock; Ana Paula Pellegrino (EconomiA, 2021)
How do changes in mobility impact crime? Using police precinct-level daily crime statistics and shootings data from the state of Rio de Janeiro, Brazil, we estimate that extortion, theft, and robberies decrease by at least 41.6% following COVID-19 mandated stay-at-home orders and changes in mobility in March 2020. Conversely, we find no change in violent crimes, despite fewer people being on the streets. To address the relationship between crime and mobility, we use cellphone data and split the precincts into subgroups by pre-Covid-19-related restrictions mobility quintiles. We estimate a similar average decrease in extortion regardless of a precinct's previous activity level, but find that the decrease in theft and robberies is substantially higher for the more mobile precincts while it disappears for the least mobile precincts. Using daily cellphone mobility data aggregated at the police precinct level, we find that changes in mobility while the stay-at-home order is in place only have a meaningful effect on robberies, which increase in likelihood when a precinct's mobility ranking is higher than the previous day. Together, these results suggest that the stay-at-home order and associated decline in mobility strongly affected extortion and property crimes while not interfering with the dynamics of violent crime. These findings support the hypothesis that violent and property crime follow different dynamics, particularly where there is a bigger impact of organized criminal groups.
Keywords: 330; Covid-19; Crime; Extortion; Organized crime; Violence